RELIGION AND PATRONAGE UNDER THE CHALUKYAS OF KALYANI - Shubha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The religious and cultural landscape of medieval South India was significantly shaped by the Chalukyas of Kalyani A syncretic approach to governance was demonstrated by their patronage of various religious traditions, such as Buddhism, Vaishnavism, Jainism, and Shaivism. During their reign, temples and other places of worship flourished, and notable architectural contributions were made by the Mahadeva Temple in Itagi and the Virupaksha Temple in Pattadakal. In addition to building magnificent temple complexes, the Chalukyan kings also established endowments for religious leaders, scholars, and ascetics. In order to comprehend the dynasty’s function in promoting religious plurality and establishing political power via sacred legitimacy, this study examines the nature of religious patronage under the Chalukyas of Kalyani through an analysis of inscriptions, temple architecture, and literary sources.